E agora você me viu? Percursos comentados de uma pessoa com deficiência na UFAL - Santos, Diego Januário dos (2019)
This study seeks to analyze the performance activities about accessibility of a student with disabilities in the university, based on their daily experiences. If for a student to stay in university amid tests, readings, family pressure, among other aspects, it may seem difficult for a student with disabilities, in addition to these issues, to move to university safely and becomes a barrier to the quality of its stay in the university space. The accessible architecture of public spaces, especially the university, becomes necessary for students with disabilities to feel safe and welcomed, besides being a precondition for their stay in the university space. The problem of this study is what are the performance activities about accessibility produced during university courses and experiences of a disabled person at UFAL, from the commented route? The objectives of the research are based on analyzing the performance of this student on accessibility, characterizing the paths made by him during his stay at the university and verifying how accessibility relations occur between the student and university space. Therefore, the methodology of the commented route was chosen in which, through five paths of a blind student of the Federal University of Alagoas, the data of this study were produced. The data show, among other points, that the statements produced by the student during the research reveal that accessibility is still a challenge for the university and a barrier for him to feel autonomous and safe during his activities within University physical space.